(untitled) (Bangladesh Journal of Zoology, 2010)
The experiment was carried out from July 2007 to June 2008, on eight water bodies of Bakerganj district under Barisal division in Bangladesh. The samples for zooplankton were taken by hydrobiological bottle from the surface water of the ponds and were filtered through plankton net and concentrated into 50 ml. The total amount of 100 liter of water was filtered for each sample. The qualitative zooplankton analysis showed the presence of 47 taxa from five groups: Protozoa (four taxa), Rotifera (31 taxa), Copepoda (five taxa), Cladocera (five taxa) and Ostracoda (two taxa). The groups of Rotifera and Copepoda (Both nauplii, larva and adult) were the main constituents of zooplankton community that was characterized by the dominance of the species: Brachionus angularis, B. forficula, Keratella tropica, Polyarthra spp., Asplanchna sp., Fillinia spp., Cyclops spp. and Diaptomus spp. Results of qualitative analysis showed that the total number of zooplankton was found to be highest in a pond (1867 ind/l; site no. 4) and the lowest in the Tulatali river (153 ind/l; site no 5). It is evident from this study that the zooplankton groups showed variations in the selected ponds. The variation depends on the different parameters that exist in the pond ecosystem. Bangladesh J. Zool. 38(1): 127-132, 2010